The impact of FX central bank intervention in a noise trading framework - Michel Beine; Paul De Grauwe; Marianna Grimaldi (Center for Economic Studies and ifo Institute (CESifo), 2005)
In this paper we investigate the effects of central bank interventions (CBI) in a noise trading model with chartists and fundamentalists. We first estimate a model in which chartists extrapolate past returns and fundamentalists forecast a mean reverting dynamics of the exchange rate towards a fundamental value. Then, we investigate the role of central bank interventions in explaining the switching properties between the two types of agents. We find evidence that in the medium run, interventions increase the proportion of fundamentalists and therefore exert some stabilizing influence on the exchange rate.
Keywords: F31; F33; 330; Wechselkurspolitik; Devisenhandel; Noise Trading; Wertpapieranalyse; Schätzung; Wechselkurs; Volatilität; Theorie; EU-Staaten; USA